Encapsulation of biocides by cyclodextrins: toward synergistic effects against pathogens - Nardello-Rataj, Véronique; Leclercq, Loïc (Beilstein Journal of Organic Chemistry, 2014)
Host–guest chemistry is useful for the construction of nanosized objects. Some of the widely used hosts are probably the cyclodextrins (CDs). CDs can form water-soluble complexes with numerous hydrophobic compounds. They have been widespread used in medicine, drug delivery and are of interest for the biocides encapsulation. Indeed, this enables the development of more or less complex systems that release antimicrobial agents with time. In this paper, the general features of CDs and their applications in the field of biocides have been reviewed. As the key point is the formation of biocide–CD inclusion complexes, this review deals with this in depth and the advantages of biocide encapsulation are highlighted throughout several examples from the literature. Finally, some future directions of investigation have been proposed. We hope that scientists studying biocide applications receive inspiration from this review to exploit the opportunities offered by CDs in their respective research areas.
Keywords: cyclodextrin; biocide; encapsulation; host–guest chemistry; pathogen; textile